2014 IEEE Spoken Language Technology Workshop (SLT) 2014
DOI: 10.1109/slt.2014.7078569
|View full text |Cite
|
Sign up to set email alerts
|

Learning hidden unit contributions for unsupervised speaker adaptation of neural network acoustic models

Abstract: This paper proposes a simple yet effective model-based neural network speaker adaptation technique that learns speakerspecific hidden unit contributions given adaptation data, without requiring any form of speaker-adaptive training, or labelled adaptation data. An additional amplitude parameter is defined for each hidden unit; the amplitude parameters are tied for each speaker, and are learned using unsupervised adaptation. We conducted experiments on the TED talks data, as used in the International Workshop o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
202
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(204 citation statements)
references
References 34 publications
2
202
0
Order By: Relevance
“…In most corpora, the training speakers differ from the test speakers. This is widely recognized as good practice and many solutions are available to improve robustness to this mismatch (Gales, 1998;Shinoda, 2011;Karafiát et al, 2011;Swietojanski and Renals, 2014). By contrast, the acoustic conditions of the training data often match (or cover) those of the test data.…”
Section: Introductionmentioning
confidence: 99%
“…In most corpora, the training speakers differ from the test speakers. This is widely recognized as good practice and many solutions are available to improve robustness to this mismatch (Gales, 1998;Shinoda, 2011;Karafiát et al, 2011;Swietojanski and Renals, 2014). By contrast, the acoustic conditions of the training data often match (or cover) those of the test data.…”
Section: Introductionmentioning
confidence: 99%
“…Learning hidden unit contribution (LHUC) is a method that linearly re-combines hidden units in a speaker-or environmentdependent manner [14,25]. Given adaptation data, LHUC rescales the contributions (amplitudes) of the hidden units in the model without actually modifying their feature receptors.…”
Section: Learning Hidden Unit Contributionmentioning
confidence: 99%
“…Similar approaches have been proposed independently in [12] and [13]. Researchers have also introduced learning hidden unit contribution (LHUC) to weight hidden unit activations in a speaker-or environment-dependent manner [14]. It was shown that LHUC results in consistent WER reductions for speaker and environment adaptation [15].…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, a deep multilayer neural network is used for the object recognition [12][13][14]. Its learning rule is to apply the steepest descend method to adjust the weights and thresholds of the neural network according to the minimum sum of the square error.…”
Section: Object Recognitionmentioning
confidence: 99%